2016
DOI: 10.18632/oncotarget.12298
|View full text |Cite
|
Sign up to set email alerts
|

Case-specific potentiation of glioblastoma drugs by pterostilbene

Abstract: Glioblastoma multiforme (GBM, astrocytoma grade IV) is the most common malignant primary brain tumor in adults. Addressing the shortage of effective treatment options for this cancer, we explored repurposing of existing drugs into combinations with potent activity against GBM cells. We report that the phytoalexin pterostilbene is a potentiator of two drugs with previously reported anti-GBM activity, the EGFR inhibitor gefitinib and the antidepressant sertraline. Combinations of either of these two compounds wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 59 publications
(77 reference statements)
0
11
0
Order By: Relevance
“… 4 In brain tumor research, these primary GC cultures have emerged as a standard model to study drug sensitivity and identify new molecular targets. 5 , 27–30 Considerable effort has been invested in supporting the representivity of primary GC cultures and comparing cell cultures isolated from the same tumor. 2–4 By comparison, we have relatively little information on the temporal evolution of GC cultures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 4 In brain tumor research, these primary GC cultures have emerged as a standard model to study drug sensitivity and identify new molecular targets. 5 , 27–30 Considerable effort has been invested in supporting the representivity of primary GC cultures and comparing cell cultures isolated from the same tumor. 2–4 By comparison, we have relatively little information on the temporal evolution of GC cultures.…”
Section: Discussionmentioning
confidence: 99%
“… 2 Compared with traditional tissue culture models, GC cultures retain cells transcriptionally similar to the tumor of origin, and retain properties important for the study of tumor regeneration. 3 One promising application of GCs is based on their potential to facilitate functional studies on cells across a population of patients 4 , 5 (eg, to determine biomarkers of drug response). For such studies to be efficient, however, it is necessary to consider the stability of the GC cultures, and the possible impact of time-dependent fluctuations in clonal substructure.…”
mentioning
confidence: 99%
“…In a previous study, we explored the benefits of PTE in attenuating inflammation and oxidative injury following subarachnoid hemorrhage and reducing mitochondrial oxidative stress after cerebral IR (11, 12). Other studies have also demonstrated the potent neuromodulatory effect of PTE on aging, Alzheimer's disease, and glioblastoma (13, 14). However, the role of PTE in modulating astrocyte-mediated inflammatory injury following cerebral IR has not been previously investigated.…”
Section: Introductionmentioning
confidence: 96%
“…After 72h incubation alamarBlueâ cell viability reagent (Thermo Fisher Scientific) was added and fluorescent readout made by Wallac 1420 Victor2 (Perkin Elmer). The resulting viability data was used to compute Combination Index scores as previously described (Schmidt et al, 2016). For further validation in a 3D tumor model over an extended time period, combinations of bortezomib with navitoclax or milciclib were selected for treatment of one bortezomib sensitive and one bortezomib resistant cell culture over 10 days.…”
Section: Modulation Of Proteasome Inhibitor Responses By Heat Antioxmentioning
confidence: 99%